P21 Advance care planning facilitator training for medical students: more than a drop in the ocean. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Götze, K; In der Schmitten, J; Fuchs, A
Abstract : Background: Healthcare professionals (HCP) often feel insecure and therefore hesitate to start ACP conversations with patients. And patients often feel reluctant to initiate ACP-conversations. Trying to discontinue this vicious circle we developed an elective ACP course for medical students. Methods: The course was developed on the base of the German facilitator-curriculum, which was revised in 2017 to include intensive role-play supported by the use of standardized-patients (SP). We adapted the facilitator curriculum to the students' experience and early stage of medical training. Course preparation comprised a letter of motivation and 10 CME questions referring to an ACP journal paper. The course is divided into 2 parts, each lasting 32 hours and including 10 hours of SP-training in groups of 2 or 3. Results: In August 2018, 7 students joined part 1 of the new ACP-course. All 7 students were in their 2nd year of medical training, the age range was 20–42 yrs, 3 were female. 5 happened to have a Muslim background which added an unexpected cultural component to the course. 4 had worked in other disciplines in healthcare before. Their motivation to participate ranged from traumatizing personal experiences to practical reasons. Their attitudes towards patient-centeredness and ACP-facilitation strongly changed from a traditional-paternalistic towards an autonomy-oriented view. At the end, student performance varied from moderate to very good. Conclusion(s): Discussing legal and ethical basics of ACP conversations, and practicing ACP with SP, were judged by the students as highly relevant, both personally and professionally.